Characterisation of Rb and Cs spin-exchange optical pumping for application to hyperpolarised 129Xe functional lung MRI - Birchall, Jonathan R. (2017)
When performing nuclear magnetic resonance (NMR) it is desirable to maximise the available polarisation of the spin system in order to achieve optimal signal-to-noise ratios. One method of achieving this is via the process of spin-exchange optical pumping (SEOP). SEOP can be used to produce hyperpolarised (HP) noble gases, which possess numerous applications in the fields of science and medicine, ranging from spectroscopic imaging of porous media to Magnetic Resonance Imaging (MRI) of the human lungs. The SEOP process involves transfer of angular momentum from circularly polarised laser photons to the electrons of an alkali metal vapour. Noble gas nuclei can then be polarised via collisions with the alkali metal vapour. Ultra-low frequency Raman Spectroscopy may be used to perform rotational temperature measurements of a nitrogen buffer gas in these SEOP experiments in real-time, in an attempt to understand the poorly understood and highly complex system dynamics and energy transport processes.